(Re)Conceiving 'Creative Drama': an exploration and expansion of American metaphorical paradigms - Woodson, Stephani Etheridge (Research in drama education, 1999)
This article considers two ontological metaphors underlying the American paradigm of creative drama' and examines them intertextually within the larger context of the child drama field. Historically, the American child drama field has associated more with education than with theatre studies, thus drawing more theory from pedagogical practices and from developmental psychology than from the theatre arts and/or performance studies. American child drama practitioners, as a whole, also have been more concerned with the practice and methodology of drama rather than the theorising of it. The historical definition of 'creative drama' developed by Americans, then, depends on two metaphorical constructions: (1) 'creative drama' is different from theatre and (2) the conflation of 'creative drama' with the construct of childhood development. Building upon the deconstruction of the nature of 'creative drama', the second part of this article is a practical application of performance (as defined by Richard Schechner) and reception theories to an understanding of 'audience'. Seen through the lens of performance theory, improvisation or 'creative drama' is not a separate or developmental state/form leading to the ability to fluidly shift mental states in formalised 'theatre'. Fundamentally, then, 'creative drama' and 'children's theatre' are not different in kind. Examining 'creative drama' through the lens of performance theory raises interesting implications for understanding, methodology, and future research.